Análisis de los consumos históricos de agua potable en el cantón Ibarra - Caicedo Corozo, Alex Manuel (2022)
Bayas (2018) presumes that “THE DRINKING WATER SYSTEMS DESIGNS MANUAL IN ECUADOR” are being over- and undersized. The CPE INEN 005-9- 1 standard used by engineers to carry out designs is ambiguous and it has not received any important reparations in water sources for more than 30 years. For this reason, the same standard recommends to carrying out specific fields studies in each village, cantons, towns, etc., in order to take into account that national realities that will help to have safe drinking water. This research took advantage of the historical water consumption records of the Ibarra canton, which was defined as a value of coefficient variation that can be used in future designs of drinking water systems in Ibarra. In addition, the present research work contributes to the development of this project "The variation in drinking water consumption in town with less than 150,000 inhabitants in Ecuador." The study a quantitative structured method and statistical evaluation tools were used (Minitab) The following were taken: Normality and homoscedasticity tests, Analysis of variances, Tukey tests, Interval diagrams and Descriptive diagrams. The results show a decrease in the consumption of drinking water in Ibarra that is the result of several factors. The value of the coefficient of variation of consumption (Kd) found for the Ibarra canton is different from the one mentioned in the INEN standard due it is outside the range 1.3 to 1.5.